The Court of Justice of the European Union : Subsidiary and Proportionality. - Shaw, Kate (Nijhoff Studies in European Union Law Ser., 2018)
In the Court of Justice of the European Union, Subsidiarity and Proportionality Kate Shaw sets out how a subsidiarity and proportionality review applied to competences could be anchored by the Court of Justice when balancing the competing interests in cases concerning the residency rights of EU citizens. The book also considers the extent to which a court which is dedicated to enhancing the European project is really able to be an independent arbiter between the EU and the Member States in this context. Both the legal reasoning of the Court and the controversial nature of residency rights of EU citizens are legally and politically very topical at the moment and of interest to legal academics and law students.